Twitter and Online Trust: Ganjar Pranowo and Anies Baswedan Towards the 2024 Presidential Election - Yahya, Muhammad; Syukri, Syukri; Syarif, Ahmad; Arni, Arni; Manggaga, Indah Pratiwi; Baharuddin, Tawakkal (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Leading up to the Presidential Election, Anies Baswedan and Ganjar Pranowo have influenced voters’ political attitudes on Twitter and demonstrated strengthening public trust in both, showing trust’s critical role in the democratization process. This research explores the relationship between Twitter use and online trust in the two candidates in the context of preparations for the 2024 presidential election in Indonesia. This research uses a quantitative approach with sentiment analysis on data from Twitter, which focuses on searching for the keywords #aniesbaswedan (17,998 Tweets) and #ganjarpranowo (17,918 Tweets) to understand the opinions, attitudes, and emotions contained in the text. These findings show that there is potential to transform public trust online. If the candidate uses Twitter effectively and succeeds in building online trust, this can provide an advantage for the candidate in their efforts to achieve victory in the 2024 Presidential Election. Ganjar Pranowo is more dominant in influencing the level of public trust in Twitter to be relatively positive, although Ganjar Pranowo also received quite a negative response. Meanwhile, Anies Baswedan needs to be more dominant to influence public trust on Twitter. The dominant factors affecting the level of trust in candidates are the coalition of political parties, Israel’s rejection, and leadership. This study also found the tendency of other factors to transform trust online, including quality content, consistency, transparency, responsiveness, ethics, sharing of references, and honesty. Social media has the potential to foster political confidence online. However, this depends on how the candidate maximizes the potential of social media.Keywords: Online trust, social media, presidential election, online discussionABSTRAKMenuju Pemilihan Presiden, Anies Baswedan dan Ganjar Pranowo telah memengaruhi sikap politik pemilih di Twitter dan menunjukkan penguatan kepercayaan publik pada keduanya, memperlihatkan peran penting kepercayaan dalam proses demokratisasi. Penelitian ini bertujuan untuk mengeksplorasi hubungan antara penggunaan Twitter dan kepercayaan online terhadap kedua kandidat tersebut dalam konteks persiapan menuju Pilpres 2024 di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis sentimen pada data dari Twitter, yang difokuskan pada pencarian kata kunci #aniesbaswedan (17998 Tweets) dan #ganjarpranowo (17918 Tweets), untuk memahami pendapat, sikap, dan emosi yang terkandung dalam teks. Temuan ini menunjukkan adanya potensi dalam mentransformasikan kepercayaan publik secara daring. Jika kandidat menggunakan Twitter secara efektif dan berhasil membangun kepercayaan online, maka hal tersebut dapat memberikan keuntungan bagi kandidat dalam upaya mencapai kemenangan di Pilpres 2024. Ganjar Pranowo lebih dominan memengaruhi tingkat kepercayaan publik di Twitter menjadi relatif positif, meskipun Ganjar Pranowo juga mendapatkan respon cukup negatif. Sementara itu, Anies Baswedan dianggap tidak cukup dominan memengaruhi kepercayaan publik di Twitter. Faktor dominan yang memengaruhi tingkat kepercayaan pada kandidat adalah koalisi partai politik, penolakan Israel, dan kepemimpinan. Studi ini juga menemukan kecenderungan dari faktor lainnya untuk mentransformasikan kepercayaan secara daring di antaranya adalah konten berkualitas, konsistensi, transparansi, responsif, etika, berbagi referensi, dan kejujuran. Media sosial memiliki potensi untuk menumbuhkan kepercayaan politik secara daring. Namun, hal tersebut sangat bergantung pada bagaimana kandidat memaksimalkan potensi media sosial tersebut.Kata Kunci: Kepercayaan daring, media sosial, pemilihan presiden, diskusi daring